Changes of serofast status in HIV negative asymptomatic neurosyphilis patients after treatment - Liu, Jing; Zhao, Tian-Wei; Zhou, Chun; Yan, Hui-Wen; Lun, Wen-Hui (Frontiers in Medicine, 2022)
Serofast status after therapy in syphilis patients is a common phenomenon. A proportion of patients who have serofast status exhibit abnormal cerebrospinal fluid test results, which can be defined as asymptomatic neurosyphilis (ANS); however, it remains unclear whether ANS patients can achieve serological cure after anti-neurosyphilis treatment as quickly as other serofast patients. In this study, nontreponemal pallidum antibody serological responses were studied in ANS and serofast control patients, and the cumulative rates of serological cure in the ANS group were 9.6%, 22.1%, 25.9%, and 30.2% in 3, 6, 9 and 12 month after treatment, which were statistically higher than those of the serofast control group. The change gap in serological cure rates was even more pronounced within 6 months after treatment, but the majority of ANS patients had no change in serofast status at 12 months after treatment. Our study indicates that anti-neurosyphilis therapy can partially change the serofast status. As serofast status cannot easily be changed even under neurosyphilis treatment in the majority of patients, the pathogenesis of this condition needs further research.